Identification and biochemical analysis of a novel APOB mutation that causes autosomal dominant hypercholesterolemia. Issue 3 (13th June 2013) - Thomas, Ellen R. A.; Atanur, Santosh S.; Norsworthy, Penny J.; Encheva, Vesela; Snijders, Ambrosius P.; Game, Laurence; Vandrovcova, Jana; Siddiq, Afshan; Seed, Mary; Soutar, Anne K.; Aitman, Timothy J.
Abstract Patients with autosomal dominant hypercholesterolemia (ADH) have a high risk of developing cardiovascular disease that can be effectively treated using statin drugs. Molecular diagnosis and family cascade screening is recommended for early identification of individuals at risk, but up to 40% of families have no mutation detected in known genes. This study combined linkage analysis and exome sequencing to identify a novel variant in exon 3 of APOB (Arg50Trp). Mass spectrometry established that low‐density lipoprotein (LDL) containing Arg50Trp APOB accumulates in the circulation of affected individuals, suggesting defective hepatic uptake. Previously reported mutations in APOB causing ADH have been located in exon 26. This is the first report of a mutation outside this region causing this phenotype, therefore, more extensive screening of this large and highly polymorphic gene may be necessary in ADH families. This is now feasible due to the high capacity of recently available sequencing platforms.